The Critical Temperature of The Superconductor Having an Array of Holes - Harsojo Harsojo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2012)
The influence of external magnetic field to the critical temperature of the superconductor having an array of hole has been calculated using time dependent Ginzburg-Landau equation. The investigation is done after calculating numerically the resistance produced when the superconductor is driven by electric current and exposed under perpendicular magnetic field fie. The result indicates that the addition of lattice holes to the superconductor exposed on perpendicular magnetic field changes the critical temperature. The changes of the critical current due to the different sizes of holes are also discussed.